Comparison Effect of Garlic and Bitter Melon Extracts on Kidney Histopathology in Hyperglycemic White Rats - Hidayati, Rafidah Nur; Indahsari, Noer Kumala; Noviana, Ayu Cahyani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2026)
Background: Hyperglycemia in diabetes mellitus can cause kidney damage through oxidative stress and tubular cell degeneration. Garlic (Allium sativum) and bitter melon (Momordica charantia) are known to possess antihyperglycemic and antioxidant effects that may improve kidney tissue damage. Objective: To determine and compare the effects of garlic and bitter melon extracts on the kidney histopathology of hyperglycemic white rats (Rattus norvegicus). Methods: This laboratory experimental study employed a post-test only control group design using 24 rats divided into four groups: normal control, hyperglycemic control, garlic extract treatment, and bitter melon extract treatment. Kidney histopathological examination was conducted using Hematoxylin-Eosin staining. Results: Administration of garlic and bitter melon extracts showed improvement in kidney structure, indicated by decreased tubular cell degeneration and necrosis compared to the hyperglycemic control group. The improvement effect was more prominent in the garlic extract group. Conclusion: Both garlic and bitter melon extracts have protective effects against kidney damage induced by hyperglycemia, with the garlic extract showing the most significant improvement.